1958
DOI: 10.1021/ja01553a037
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Linear Polymers from Diene Monomers by a Cyclic Polymerization Mechanism. II. Polyacrylic Anhydride and the Derived Polyacrylic Acid1,2

Abstract: Acrylic anhydride has been polymerized in solution to afford a series of saturated, linear polymers. Values of molecular weight from a few thousand up to 95,000 were recorded for the various products. The properties of the polymers showed that polymerization had occurred by the alternating intramolecular-intermolecular mechanism, in this case leading to a poly-3(5)-methyleneglutaric anhydride structure.The polyacrylic acid obtained by hydrolysis of a polyacrylic anhydride has been shown to have a much more reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1959
1959
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…As per the "5 Å rule [G] ", 90 smaller DVMs with a short intervinyl distance, such as unconjugated 1,5-and 1,6 dienes, are inherently desirable. Following Butler's initial study on FRP of diallyldimethylammonium salts, 87,88 various 1,5-and 1,6 dienes such as (meth)acrylic anhydride, 91 divinyl acetals, 92 o-divinylbenzene 93 and diallylsilanes 94 weresubjected to FRP and the structures obtained were demonstrated to have five-and six-membered rings (Figure 5a) distributed along the C-C chains. The rapid expansion of RDRP techniques in the last two decades have greatly facilitated the synthesis of cyclopolymers with well-defined MW, low dispersity and high chain end functionalities.…”
Section: [H2] Cyclopolymersmentioning
confidence: 99%
“…As per the "5 Å rule [G] ", 90 smaller DVMs with a short intervinyl distance, such as unconjugated 1,5-and 1,6 dienes, are inherently desirable. Following Butler's initial study on FRP of diallyldimethylammonium salts, 87,88 various 1,5-and 1,6 dienes such as (meth)acrylic anhydride, 91 divinyl acetals, 92 o-divinylbenzene 93 and diallylsilanes 94 weresubjected to FRP and the structures obtained were demonstrated to have five-and six-membered rings (Figure 5a) distributed along the C-C chains. The rapid expansion of RDRP techniques in the last two decades have greatly facilitated the synthesis of cyclopolymers with well-defined MW, low dispersity and high chain end functionalities.…”
Section: [H2] Cyclopolymersmentioning
confidence: 99%
“…Yield was 1.01 g. The cyclized polymerization has been studied since A. Crawshaw and G. B. Butler reported. [ 13 ] The copolymerization proceeded to form the cyclic structure in the main chain. This polymerization was high reactivity to radical initiator and the cyclized polymer was easily obtained.…”
Section: Preparation Of Chdmamentioning
confidence: 99%
“…It is indeed unfortunate that the initial work in this field, which so admirably demonstrated the presence of cyclic structures, has been interpreted as demonstrating that the cyclic structures contained 6-membered rings. In the polymer derived from the quaternary ammonium derivative of diallylamine, Butler et al [27,28] clearly demonstrated the presence of cyclic structures by chemical degradation of the polymer as shown in Figures 5 and 6. However, it should be clear from the reactions shown that no conclusion should have been drawn regarding the ring size.…”
Section: Ring Size In Cyclopolymers From Diallylaminesmentioning
confidence: 99%
“…Attempts to degrade polydiallylamines using the methods of Butler [27,28] and other methods, did not proceed in a manner that permitted the identification of ring size. These methods were not pursued because of the promising results obtained with 13C nuclear magnetic resonance (NMR) spectroscopy.…”
Section: Structure Of the Polymers From Diallylaminesmentioning
confidence: 99%